Effect of nutritional status on wound healing after coronary artery bypass graft (CABG) surgery - Zaffar, Muazama; Asma Afreen; Waseem, Muhammad; Ahmed, Zaheer (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the pre-operative nutritional status and its effect on wound healing of patients having undergone coronary artery bypass graft surgery. Method: The hospital-based prospective study was conducted at the Armed Forces Institute of Cardiology/National Institute of Heart Disease, Rawalpindi, Pakistan, from October 2017 to March 2018, and comprised patients who underwent coronary artery bypass graft surgery. Sternal wound healing as an outcome measure was assessed with nutritional status. Investigation of dietary data focussed on various food groups and their impact on wound healing. Data was analysed using SPSS 21. Results: Of the 330 patients, 16 (4.8%) died within hospital. The final sample, as such, comprised 314(95.2%) patients; 273 (86.9%) males and 42 (13.1%) females, with an overall mean age of 56.6±8.3 years. The mean body mass index was 26.9±4.3kg/m². There was non-significant relationship between body mass index and wound healing (p>0.05). Significant relationship was observed between albumin, blood glucose and wound healing (p<0.05). Conclusion: Low levels of albumin and poor blood glucose control before surgery was found to be associated with delayed wound healing. Nutritional intervention prior to coronary artery bypass graft surgery may lead to reduced risk and complications during / after surgery.